Catalytic layer and preparation method and application thereof
By using carbon monoxide as a shielding agent in the membrane electrode catalytic layer, the problem of disordered pores and substance distribution in the catalytic layer is solved, the catalyst utilization rate is improved and the mass transfer resistance is reduced, and the performance of the hydrogen-electric conversion device is significantly improved. .
Patent Information
- Application Number
- CN202411480445.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-02-18
AI Technical Summary
The pores and substance distribution in the existing membrane electrode catalytic layer are disordered, resulting in low catalyst utilization and large mass transfer resistance, which affects the performance of the hydrogen-electric conversion device.
Carbon monoxide is used as a shielding agent, and the catalyst in the raw material component of the catalyst is adsorbed and mixed to form a catalyst slurry, and a catalyst layer is obtained by drying. This method occupies the catalytic site of the catalyst in advance, reduces the interaction between the catalyst and the sulfonic acid group, promotes uniform distribution of ionomers, and improves proton conduction and gas transport capabilities.
By ordering the distribution of pores and substances in the catalytic layer, the utilization rate of the catalyst is improved, the mass transfer resistance is reduced, the electrochemical performance of the membrane electrode is improved, and the overall performance of the hydrogen-electric conversion device is enhanced.
Smart Images

Figure CN119456041A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of membrane electrode catalyst layer preparation, and in particular to a catalyst layer and a preparation method and application thereof. Background Art
[0002] Hydrogen-to-electricity conversion measures such as water electrolysis and fuel cells can be combined with new energy power generation to solve the problems of power abandonment and grid connection of new energy power generation, and at the same time, it is conducive to the optimization of hydrogen production structure in the hydrogen energy industry. Proton exchange membrane water electrolysis (PEMWEs) and proton exchange membrane fuel cells (PEMFCs) using polymer electrolyte membrane as proton conductor and platinum group metals (Pt, Pd, Ir, Ru) as catalysts have the advantages of high power density, high efficiency, low operating temperature, simple operation, etc., and are the research focus of hydrogen energy development.
[0003] Improving the efficiency of hydrogen-to-electricity conversion devices and reducing operating costs are the keys to achieving their large-scale application. The membrane electrode is the core component of the hydrogen-to-electricity conversion device, and the catalyst layer is the place where the core reaction occurs. From the perspective of the intrinsic activity of the catalyst, the use of precious metals can be reduced by using carriers and preparing alloy catalysts, thereby improving the activity and stability of the catalyst and thus improving the utilization rate of the catalyst. In addition, the electrochemical reaction process mainly occurs at the three-phase interface in the catalyst layer where electrons, protons and gases can reach. Related studies have shown that uneven distribution of ionomers will affect both proton conduction and gas transport in the catalyst layer. Therefore, the mass transfer resistance in the catalyst layer is crucial to the performance of hydrogen-to-electricity conversion.
[0004] At present, from the perspective of membrane electrode and catalyst layer structure, there are three main methods to improve mass transfer resistance and enhance PEMFC performance by exploring new membrane electrode preparation methods and preparation processes: including adjustment of MEA preparation method, optimization of overall structure of catalyst layer and controllable construction of microscopic three-phase interface. MEA prepared by traditional methods such as CCS, CCM and DMD has many structural defects: random arrangement of catalyst particles, ionomers, etc. in the catalyst layer, resulting in large mass transfer resistance, low catalyst utilization, short life and serious energy loss in the catalyst layer. Ordering can improve the gas diffusion and proton and electron conduction capacity of the membrane electrode and improve the catalyst utilization, but the durability is poor, the preparation process is complex and the cost is high. Gradient and patterning can improve MEA performance, but the pores and material distribution in the catalyst layer are still disordered, and the mass transfer overpotential is still high. Therefore, it is urgent to provide a new preparation method for preparing membrane electrodes to improve the ordered state of pores and material distribution in the catalyst layer, thereby improving the utilization of the catalyst. Summary of the invention
[0005] The purpose of the present application is to provide a catalytic layer and a preparation method and application thereof, aiming to solve the problem in the prior art that the pores and material distribution in the catalytic layer of the membrane electrode are in a disordered state, resulting in too low catalyst utilization.
[0006] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:
[0007] In a first aspect, the present application provides a method for preparing a catalytic layer, comprising the following steps:
[0008] Providing carbon monoxide, and subjecting the carbon monoxide to adsorption and mixing treatment with raw material components of the catalyst layer to obtain catalyst slurry;
[0009] The catalyst slurry is coated on the surface of the transfer base film and dried to obtain a catalyst layer.
[0010] The preparation method of the catalyst layer provided in the first aspect of the present application, the preparation method uses carbon monoxide as a shielding agent, because carbon monoxide and the catalyst in the catalyst layer raw material component have the effect of mutual adsorption, carbon monoxide is used to occupy the catalyst's catalytic site in advance, protect the catalytic site, effectively weaken the strong interaction between the catalyst and the sulfonic acid group, and avoid the large-scale aggregation of ionomers on the catalyst surface, avoid causing a large gas mass transfer resistance, promote the uniform distribution of ionomers on the catalyst surface, so that proton conduction is no longer limited, and the pores and material distribution in the catalyst layer are ordered, which is conducive to improving the utilization rate of the catalyst. In addition, carbon monoxide, as a gas, can be completely removed by electrochemical scanning after the membrane electrode is prepared, and the product will not poison the catalytic site for the second time, and will not remain in the catalyst layer to affect the performance and stability of the hydrogen-to-electricity conversion device; therefore, the preparation method is simple and fast, can effectively improve the catalytic performance of the catalyst layer, and is conducive to wide application.
[0011] In some embodiments, the amount of carbon monoxide introduced is ≥ 0.1 L / g, and the introduction time is ≥ 24 hours.
[0012] In some embodiments, the raw material components of the catalytic layer include a catalyst, an ionomer, and a solvent; and the mass ratio of the catalyst, the ionomer, and the solvent is 1:0.1-3:10-100.
[0013] In some embodiments, the catalyst includes a catalyst containing at least one metal of Pt, Pd, Ir, Ru.
[0014] In some embodiments, the ionomer includes a polymer containing sulfonic acid groups.
[0015] In some embodiments, the solvent includes at least one of n-propanol, isopropanol, anhydrous ethanol, dipropylene glycol, ethylene glycol, n-hexane, and cyclohexane.
[0016] In some embodiments, the polymer containing sulfonic acid groups includes at least one of Solvy-D790, Du Pont-D2020, and DuPont-D520.
[0017] In some embodiments, the step of adsorbing and mixing carbon monoxide with the raw material components of the catalyst layer includes:
[0018] The carbon monoxide and the catalyst in the raw material components are first adsorbed and then mixed with other components to obtain a catalyst slurry;
[0019] or,
[0020] The raw material components of the catalyst layer are mixed uniformly to obtain a raw material mixture of the catalyst layer, and then the carbon monoxide and the raw material mixture of the catalyst layer are adsorbed to obtain a catalyst slurry.
[0021] In some embodiments, in the step of coating the catalyst slurry on the surface of the transfer base film, the coating includes spray coating or knife coating.
[0022] In some embodiments, the drying process is performed at a temperature of 50 to 90° C. and for a time of 10 to 60 minutes.
[0023] In a second aspect, the present application provides a catalytic layer prepared by the above-mentioned method for preparing a catalytic layer.
[0024] The catalytic layer provided in the second aspect of the embodiment of the present application is prepared by the above-mentioned method for preparing the catalytic layer. Therefore, the pores and material distribution in the obtained catalytic layer are ordered, it has good electrical properties, and can be used to prepare membrane electrodes.
[0025] In a third aspect, the present application provides a method for preparing a membrane electrode, comprising the following steps: assembling the above-mentioned catalytic layer with a proton exchange membrane and a gas diffusion layer, and then performing a degassing treatment using an electrochemical method to obtain a membrane electrode.
[0026] The third aspect of the embodiment of the present application provides a method for preparing a membrane electrode, which uses the above-mentioned catalytic layer to prepare the membrane electrode, and after assembling the membrane electrode, an electrochemical method is used to remove the occupied carbon monoxide to ensure that the carbon monoxide does not remain in the catalytic layer. In addition, since the membrane electrode contains the above-mentioned catalytic layer, it has a higher peak power, which is beneficial to improving the overall performance of the hydrogen-to-electricity conversion device.
[0027] In a fourth aspect, the present application provides an application of a membrane electrode prepared by the above-mentioned membrane electrode preparation method in a water electrolysis device or a fuel cell. In a fourth aspect of the present application, an embodiment provides an application of a membrane electrode prepared by the above-mentioned membrane electrode preparation method in a water electrolysis device or a fuel cell; the obtained water electrolysis device has excellent water electrolysis performance, and the fuel cell has excellent electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0029] Figure 1 This is an analysis chart of the water electrolysis performance test results of the Ir-containing catalyst obtained in Example 1 and Comparative Example 1 of the present application.
[0030] Figure 2 It is an analysis chart of the results of the performance test of the membrane electrode assembly containing Pt catalyst as a fuel cell obtained in Example 2 and Comparative Example 2 of the present application. DETAILED DESCRIPTION
[0031] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail in conjunction with the embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0032] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0033] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0034] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0035] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0036] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass in the embodiment description of the present application can be μg, mg, g, kg and other mass units known in the chemical industry.
[0037] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0038] The commonly used proton conductor and binder in the catalyst layer of the hydrogen-to-electricity conversion device is perfluorosulfonic acid (PFSA). The sulfonate groups on perfluorosulfonic acid have a strong interaction with the commonly used platinum group catalysts (Pt, Pd, Ir, Ru), which will cause the ionomers to accumulate on the catalyst surface during the slurry preparation process, bury the catalytic sites, and reduce the catalytic activity.
[0039] Related studies on the distribution of ionomers in the catalyst layer have shown that uneven distribution of ionomers will affect both proton conduction and gas transport in the catalyst layer. Reducing the ionomer content can improve gas mass transfer, while uniform dispersion of ionomers ensures proton conduction. However, even if the ionomers on the catalyst surface are evenly distributed so that proton conduction is no longer restricted, the interfacial mass transfer resistance between the catalyst and the ionomer still seriously affects the catalytic activity.
[0040] The main source of gas mass transfer resistance in the catalytic layer is the interaction between the sulfonic acid groups on the ionomer and the catalyst. The sulfonic acid groups occupy the catalytic sites, resulting in reduced catalytic activity. At the same time, this interaction also fixes the ionomer chain, reducing its degree of freedom, which is not conducive to the diffusion of gas in the ionomer.
[0041] In view of the above problems, the first aspect of the embodiment of the present application provides a method for preparing a catalytic layer, comprising the following steps:
[0042] S01 provides carbon monoxide, the carbon monoxide and the raw material components of the catalyst layer are adsorbed and mixed to obtain a catalyst slurry;
[0043] S02. Coat the catalyst slurry on the surface of the transfer base film, dry it, and obtain a catalyst layer.
[0044] The preparation method of the catalyst layer provided in the first aspect of the present application, the preparation method uses carbon monoxide as a shielding agent, because carbon monoxide and the catalyst in the catalyst layer raw material component have the effect of mutual adsorption, carbon monoxide is used to occupy the catalyst's catalytic site in advance, protect the catalytic site, effectively weaken the strong interaction between the catalyst and the sulfonic acid group, and avoid the large-scale aggregation of ionomers on the catalyst surface, avoid causing a large gas mass transfer resistance, promote the uniform distribution of ionomers on the catalyst surface, so that proton conduction is no longer limited, and the pores and material distribution in the catalyst layer are ordered, which is conducive to improving the utilization rate of the catalyst. In addition, carbon monoxide, as a gas, can be completely removed by electrochemical scanning after the membrane electrode is prepared, and the product will not poison the catalytic site for the second time, and will not remain in the catalyst layer to affect the performance and stability of the hydrogen-to-electricity conversion device; therefore, the preparation method is simple and fast, can effectively improve the catalytic performance of the catalyst layer, and is conducive to wide application.
[0045] In step S01, carbon monoxide is provided, and the carbon monoxide is adsorbed and mixed with the raw material components of the catalyst layer to obtain a catalyst slurry.
[0046] In some embodiments, the amount of carbon monoxide introduced is ≥0.1L / g, and the introduction time is ≥24 hours. Controlling the amount of carbon monoxide introduced and the introduction time ensures that the amount of carbon monoxide introduced is sufficient, which is conducive to forming a placeholder for the catalytic site of the metal catalyst and achieving a better protective effect; at the same time, the strong interaction between the catalyst and the sulfonic acid group is weakened, while avoiding the large-scale aggregation of ionomers on the catalyst surface, avoiding the formation of a large gas body resistance, promoting the uniform distribution of ionomers on the catalyst surface, and improving the utilization rate of the catalyst. If the amount of introduction is too small or the introduction time is insufficient, it will cause carbon monoxide to be difficult to form sufficient adsorption on the catalytic site of the catalyst, thereby affecting the catalytic activity of the catalyst.
[0047] In some embodiments, the raw material components of the catalyst layer include a catalyst, an ionomer, and a solvent; and the mass ratio of the catalyst, the ionomer, and the solvent is 1:0.1 to 3:10 to 100. Accurately controlling the mass ratio of the catalyst, the ionomer, and the solvent can achieve the free distribution of the sulfonic acid ionomer during the slurry preparation process, avoiding its large aggregation on the catalyst surface, causing a large gas mass transfer resistance. Since the content of the ionomer has an important influence on the structure of the catalyst layer, especially when the amount of ionomer added is too much, the ionomer will have a more obvious embedding effect on the catalytic site of the catalyst, and will cause excessive ionomer accumulation in the catalyst layer to hinder water vapor transmission.
[0048] In the preparation process of specific embodiments, the selection of different catalysts, solvents and ionomers is determined by different catalytic layers and process requirements. For example, the solvent content requirements for spraying and scraping are different, and the electrolytic water catalytic layer and the fuel cell catalytic layer have different ionomer content requirements; therefore, it is necessary to provide corresponding contents in the specific process.
[0049] In some embodiments, the catalyst includes a catalyst containing at least one metal of Pt, Pd, Ir, Ru.
[0050] In some embodiments, the ionomer includes a polymer containing sulfonic acid groups. In some embodiments, the polymer containing sulfonic acid groups includes at least one of Solvy-D790, Du Pont-D2020, and Du Pont-D520.
[0051] In some embodiments, the solvent includes at least one of n-propanol, isopropanol, anhydrous ethanol, dipropylene glycol, ethylene glycol, n-hexane, and cyclohexane.
[0052] In some embodiments, the adsorption and mixing of carbon monoxide with the raw material components of the catalyst layer can be accomplished by two different methods.
[0053] In some specific embodiments, the step of adsorbing and mixing carbon monoxide with the raw material components of the catalyst layer includes: first adsorbing carbon monoxide with the catalyst in the raw material components, and then mixing with other components to obtain a catalyst slurry. In this method, when carbon monoxide adsorbs the catalyst, only carbon monoxide and the catalyst exist, and there is no competition with the ionomer and the solvent for the catalyst interaction; carbon monoxide can completely achieve a full range of adsorption and coating treatment on the catalyst.
[0054] In some embodiments, the process of first subjecting carbon monoxide to adsorption treatment with the catalyst in the raw material component also includes: first pre-treating the catalyst in the raw material component to remove impurities adsorbed on its surface. Ensure that the subsequent carbon monoxide can be stably adsorbed in the catalytic site. In some specific embodiments, the pretreatment includes: placing in a tubular furnace, passing a hydrogen / argon mixture, and heating to 200-220°C for catalyst reduction. Ensure that the impurity molecules on the surface of the catalyst are completely removed, and the oxidized catalytic sites on the surface are reduced to a zero-valent state, thereby enhancing the adsorption effect of CO on its surface.
[0055] In other specific embodiments, the step of adsorbing and mixing carbon monoxide with the raw material components of the catalyst layer includes: uniformly mixing the raw material components of the catalyst layer to obtain a raw material mixture of the catalyst layer, and then adsorbing carbon monoxide with the raw material mixture of the catalyst layer to obtain a catalyst slurry. In this method, the raw materials are first mixed to obtain a slurry, and then carbon monoxide is introduced into the slurry. This method can also achieve adsorption of the catalyst.
[0056] In some embodiments, in the step of uniformly mixing the raw material components of the catalytic layer to obtain a raw material mixture for the catalytic layer, the uniform mixing treatment method includes but is not limited to any one of ball milling, magnetic stirring, water bath ultrasound, cell disruption and high-speed shearing.
[0057] In step S02, the catalyst slurry is coated on the surface of the transfer base film and dried to obtain a catalyst layer.
[0058] In some embodiments, in the step of coating the catalyst slurry on the surface of the transfer base film, the coating includes spray coating or knife coating.
[0059] In some embodiments, the drying process is performed at a temperature of 50 to 90° C. and for a time of 10 to 60 minutes.
[0060] In a second aspect, the present application provides a catalytic layer prepared by the above-mentioned method for preparing a catalytic layer.
[0061] The catalytic layer provided in the second aspect of the embodiment of the present application is prepared by the above-mentioned method for preparing the catalytic layer. Therefore, the pores and material distribution in the obtained catalytic layer are ordered, it has good electrical properties, and can be used to prepare membrane electrodes.
[0062] In a third aspect, the present application provides a method for preparing a membrane electrode, comprising the following steps: assembling the above-mentioned catalytic layer with a proton exchange membrane and a gas diffusion layer, and then performing a degassing treatment using an electrochemical method to obtain a membrane electrode.
[0063] The third aspect of the embodiment of the present application provides a method for preparing a membrane electrode, which uses the above-mentioned catalytic layer to prepare the membrane electrode, and after assembling the membrane electrode, an electrochemical method is used to remove the occupied carbon monoxide to ensure that the carbon monoxide does not remain in the catalytic layer. In addition, since the membrane electrode contains the above-mentioned catalytic layer, it has a higher peak power, which is beneficial to improving the overall performance of the hydrogen-to-electricity conversion device.
[0064] In some embodiments, the step of assembling the above-mentioned catalyst layer with the proton exchange membrane and the gas diffusion layer includes: using a hot press transfer machine to transfer the catalyst layer to both sides of the proton exchange membrane under the conditions of 120-200°C, a pressure of 40 / 40PSI, and a rotation speed of 6-7FPM, and then superimposing it with the gas diffusion layer, and preparing a membrane electrode through packaging treatment.
[0065] In some embodiments, the step of using an electrochemical method for degassing includes: assembling the membrane electrode into a hydrogen-to-electricity conversion device, introducing hydrogen to the reference electrode side, introducing nitrogen to the working electrode side, applying a cyclic voltage of 0-1V, and removing CO adsorbed on the catalyst for 5 to 6 cycles.
[0066] In a fourth aspect, the present application provides the use of a membrane electrode prepared by the above-mentioned membrane electrode preparation method in a water electrolysis device or a fuel cell.
[0067] The fourth aspect of the present application provides an application of a membrane electrode prepared by the above-mentioned membrane electrode preparation method in a water electrolysis device or a fuel cell; the obtained water electrolysis device has excellent water electrolysis performance, and the fuel cell has excellent electrochemical performance. The following is an explanation in conjunction with specific embodiments.
[0068] Example 1
[0069] Preparation of catalyst layer and membrane electrode
[0070] (1) Add 0.2 g of Ir catalyst to a sample bottle, place it in a 0.03 L sealed container, evacuate it and place it for more than 3 hours, then fill it with pure CO to atmospheric pressure and maintain it for more than 24 hours for normal pressure adsorption to obtain CO adsorbed Ir catalyst;
[0071] (2) weighing raw materials according to a mass ratio of catalyst: ionomer: solvent of 1:0.2:50, adding Nafion resin solution and n-propanol solvent to the CO treated catalyst, respectively, and evenly dispersing them to prepare a catalyst slurry;
[0072] (3) On a clean horizontal operating table, use a spray gun or ultrasonic sprayer to evenly spray the catalyst slurry on the PTFE, and use an oven at 80°C to dry it for 10 minutes;
[0073] (4) using a hot press transfer machine, at a temperature of 150° C., a pressure of 40 / 40 PSI, and a rotation speed of 6 FPM, the catalyst layer was transferred to both sides of the proton exchange membrane, and then the membrane electrode was prepared by encapsulation;
[0074] (5) The membrane electrode was assembled into a hydrogen-to-electricity conversion device, hydrogen was introduced into the reference electrode side, nitrogen was introduced into the working electrode side, and a 0-1 V cyclic voltage was applied. CO adsorbed on the catalyst was removed by five cycles.
[0075] Example 2
[0076] Preparation of catalyst layer and membrane electrode
[0077] (1) Add 0.2 g of Ir catalyst to a sample bottle, place it in a 0.03 L sealed container, evacuate it and place it for more than 3 hours, then fill it with pure CO to atmospheric pressure and maintain it for more than 24 hours for normal pressure adsorption to obtain a CO adsorbed Pt catalyst;
[0078] (2) weighing raw materials according to a mass ratio of catalyst: ionomer: solvent of 1:0.2:50, adding Nafion resin solution and n-propanol solvent to the CO treated catalyst, respectively, and evenly dispersing them to prepare a catalyst slurry;
[0079] (3) On a clean horizontal operating table, use a spray gun or ultrasonic sprayer to evenly spray the catalyst slurry on the PTFE, and use an oven at 80°C to dry it for 10 minutes;
[0080] (4) using a hot press transfer machine, at a temperature of 150° C., a pressure of 40 / 40 PSI, and a rotation speed of 6 FPM, the catalyst layer was transferred to both sides of the proton exchange membrane, and then the membrane electrode was prepared by encapsulation;
[0081] (5) The membrane electrode was assembled into a hydrogen-to-electricity conversion device, hydrogen was introduced into the reference electrode side, nitrogen was introduced into the working electrode side, and a 0-1 V cyclic voltage was applied. CO adsorbed on the catalyst was removed by five cycles.
[0082] Example 3
[0083] Preparation of catalyst layer and membrane electrode
[0084] (1) Add 0.2 g of a platinum group catalyst into a crucible, place it in a tubular furnace, introduce a hydrogen / argon mixed gas, and heat it to 200° C. to perform a catalyst reduction treatment;
[0085] (2) adding 0.2 g of the reduced platinum group catalyst into a sample bottle, placing the sample bottle in a sealed container and evacuating the container, then filling the sample bottle with pure CO until the atmospheric pressure is maintained for more than 24 hours for normal pressure adsorption to obtain a CO adsorbed platinum group catalyst;
[0086] (3) weighing raw materials according to a mass ratio of catalyst: ionomer: solvent of 1:0.2:50, adding a sulfonic acid ionomer solution and a n-propanol solvent to the CO treated catalyst, respectively, and uniformly dispersing them to prepare a catalyst slurry;
[0087] (4) On a clean horizontal operating table, use a coating machine to evenly scrape the catalyst slurry onto the PTFE, and dry it at 60°C in the coating machine for 10 minutes;
[0088] (5) using a hot press transfer machine, at a temperature of 150° C., a pressure of 40 / 40 PSI, and a rotation speed of 6 FPM, the catalyst layer was transferred to both sides of the proton exchange membrane, and a membrane electrode was prepared by encapsulation;
[0089] (6) The membrane electrode was assembled into a hydrogen-to-electricity conversion device, hydrogen was introduced into the reference electrode side, nitrogen was introduced into the working electrode side, and a cyclic voltage of 0-1 V was applied. CO adsorbed on the platinum group catalyst was removed by five cycles.
[0090] Example 4
[0091] Preparation of catalyst layer and membrane electrode
[0092] (1) 0.2 g of a platinum group catalyst was added to a sample bottle, and raw materials were weighed in a mass ratio of catalyst: ionomer: solvent of 1:0.2:50. A sulfonic acid ionomer solution and a n-propanol solvent were added respectively and uniformly dispersed. Then, pure CO gas was introduced for 10-30 min for CO adsorption, and the mixture was uniformly dispersed again to obtain a catalyst slurry.
[0093] (2) On a clean horizontal operating table, use a spray gun or ultrasonic sprayer to evenly spray the catalyst slurry on the PTFE, and use an oven at 80°C to dry it for 10 minutes.
[0094] (3) Using a hot press transfer machine, the catalyst layer was transferred to both sides of the proton exchange membrane at a temperature of 150° C., a pressure of 40 / 40 PSI, and a rotation speed of 6 FPM, and then the membrane electrode was prepared by encapsulation.
[0095] (4) The membrane electrode was assembled into a hydrogen-to-electricity conversion fixture, hydrogen was introduced into the reference electrode side, nitrogen was introduced into the working electrode side, and a 0-1 V cyclic voltage was applied. CO adsorbed on the Pt / C catalyst was removed by 5 cycles.
[0096] Comparative Example 1
[0097] Preparation of catalyst layer and membrane electrode
[0098] (1) weighing raw materials according to a mass ratio of catalyst: ionomer: solvent of 1:0.2:50, providing 0.2 g of Ir catalyst, adding Nafion resin solution and n-propanol solvent, and uniformly dispersing to prepare catalyst slurry;
[0099] (2) On a clean horizontal operating table, use a spray gun or ultrasonic sprayer to evenly spray the catalyst slurry on the PTFE, and use an oven at 80°C to dry it for 10 minutes;
[0100] (3) Using a hot press transfer machine, the catalyst layer was transferred to both sides of the proton exchange membrane at a temperature of 150° C., a pressure of 40 / 40 PSI, and a rotation speed of 6 FPM, and then the membrane electrode was prepared by encapsulation.
[0101] Comparative Example 2
[0102] Preparation of catalyst layer and membrane electrode
[0103] (1) weighing raw materials according to a mass ratio of catalyst: ionomer: solvent of 1:0.2:50, providing 0.2 g of Pt catalyst, adding Nafion resin solution and n-propanol solvent, and uniformly dispersing to prepare a catalyst slurry;
[0104] (2) On a clean horizontal operating table, use a spray gun or ultrasonic sprayer to evenly spray the catalyst slurry on the PTFE, and use an oven at 80°C to dry it for 10 minutes;
[0105] (3) Using a hot press transfer machine, the catalyst layer was transferred to both sides of the proton exchange membrane at a temperature of 150° C., a pressure of 40 / 40 PSI, and a rotation speed of 6 FPM, and then the membrane electrode was prepared by encapsulation.
[0106] Performance Testing
[0107] (I) The Ir-containing catalysts obtained in Example 1 and Comparative Example 1 were subjected to water electrolysis performance testing. The specific experimental method was as follows: the prepared Ir-containing membrane electrode was assembled into a single water electrolysis cell with an active area of 4 square centimeters. A stepwise constant current was applied to the single cell to record the corresponding voltage to obtain a polarization curve for water electrolysis.
[0108] (ii) The membrane electrode containing Pt catalyst obtained in Example 2 and Comparative Example 2 was assembled into a fuel cell, and then the performance was tested. The specific experimental method was as follows: the prepared Pt-containing membrane electrode was assembled into a fuel cell single cell with an active area of 4 square centimeters. A step constant current was applied to the single cell, and the corresponding voltage was recorded to obtain a polarization curve of water electrolysis.
[0109] Results Analysis
[0110] (I) The results of the water electrolysis performance test of the Ir-containing catalysts obtained in Example 1 and Comparative Example 1 are as follows: Figure 1 As shown, it can be seen that compared with the membrane electrode without CO treatment (Comparative Example 1), the membrane electrode after CO treatment (Example 1) requires a lower working voltage at the same current density, indicating that the CO treatment improves the ionomer distribution on the catalyst surface and the pore structure of the catalytic layer, optimizes the electron / proton transport and gas transport in the membrane electrode, and the corresponding water electrolysis efficiency is higher.
[0111] (ii) The results of the performance test of assembling the membrane electrode containing Pt catalyst obtained in Example 2 and Comparative Example 2 into a fuel cell are analyzed as follows: Figure 2As shown, it can be seen that compared with the membrane electrode without CO treatment (Comparative Example 2), the membrane electrode after CO treatment (Example 2) has a higher power at the same current density, indicating that the CO treatment improves the distribution of ionomers on the catalyst surface and the pore structure of the catalytic layer, optimizes the electron / proton transport and gas transport in the membrane electrode, and the corresponding fuel cell efficiency is higher.
[0112] In summary, the preparation method of the catalytic layer provided by the present application, the preparation method uses carbon monoxide as a shielding agent, because carbon monoxide and the catalyst in the raw material component of the catalytic layer have the effect of mutual adsorption, carbon monoxide is used to occupy the catalytic site of the catalyst in advance, protect the catalytic site, effectively weaken the strong interaction between the catalyst and the sulfonic acid group, and avoid the large-scale aggregation of ionomers on the catalyst surface, avoid causing a large gas mass transfer resistance, promote the uniform distribution of ionomers on the catalyst surface, so that proton conduction is no longer limited, and the pores and material distribution in the catalytic layer are ordered, which is conducive to improving the utilization rate of the catalyst. In addition, carbon monoxide, as a gas, can be completely removed by electrochemical scanning after the preparation of the membrane electrode, and the product will not poison the catalytic site for the second time, and will not remain in the catalytic layer to affect the performance and stability of the hydrogen-electric conversion device; Therefore, the preparation method is simple and fast, can effectively improve the catalytic performance of the catalytic layer, and is conducive to wide application.
[0113] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A method for preparing a catalytic layer, characterized in that: The steps include: Providing carbon monoxide, and subjecting the carbon monoxide to adsorption and mixing treatment with raw material components of the catalyst layer to obtain catalyst slurry; The catalyst slurry is coated on the surface of the transfer base film and dried to obtain a catalyst layer.
2. The method for preparing a catalytic layer according to claim 1, characterized in that: The amount of carbon monoxide introduced is ≥0.1 L / g, and the introduction time is ≥24 hours.
3. The method for preparing a catalyst layer according to claim 1, characterized in that: The raw material components of the catalytic layer include a catalyst, an ionomer and a solvent; and the mass ratio of the catalyst, the ionomer and the solvent is 1:0.1-3:10-100.
4. The method for preparing a catalytic layer according to claim 3, characterized in that: The catalyst comprises a catalyst containing at least one metal selected from the group consisting of Pt, Pd, Ir and Ru; and / or, The ionomer comprises a polymer containing sulfonic acid groups; and / or, The solvent includes at least one of n-propanol, isopropanol, anhydrous ethanol, dipropylene glycol, ethylene glycol, n-hexane and cyclohexane.
5. The method for preparing a catalytic layer according to claim 4, characterized in that: The polymer containing sulfonic acid groups includes at least one of Solvy-D790, Du Pont-D2020, and Du Pont-D520.
6. The method for preparing a catalytic layer according to claim 1, characterized in that: The step of adsorbing and mixing the carbon monoxide with the raw material components of the catalyst layer comprises: The carbon monoxide and the catalyst in the raw material components are first adsorbed, and then mixed with other components to obtain a catalyst slurry; or, The raw material components of the catalyst layer are mixed uniformly to obtain a raw material mixture of the catalyst layer, and then carbon monoxide and the raw material mixture of the catalyst layer are adsorbed to obtain a catalyst slurry.
7. The method for preparing a catalyst layer according to claim 1, characterized in that: In the step of coating the catalyst slurry on the surface of the transfer base film, the coating includes spray coating or blade coating; and / or, The drying process is performed at a temperature of 50 to 90° C. and for a time of 10 to 60 minutes.
8. A catalytic layer, characterized in that: The catalyst layer is prepared by the method for preparing the catalyst layer as described in any one of claims 1 to 7.
9. A method for preparing a membrane electrode, characterized in that: The method comprises the following steps: assembling the catalyst layer described in claim 8 with a proton exchange membrane and a gas diffusion layer, and then removing carbon monoxide by an electrochemical method to obtain a membrane electrode.
10. Use of a membrane electrode prepared by the membrane electrode preparation method according to claim 9 in a water electrolysis device or a fuel cell.